FORMATION OF THE FRONT-LINE KHARKIV IMAGE BY MEANS OF MEDIA - Demydiuk, Oksana; Averbakh, Mykhaylo (Sworld-Us Conference proceedings, 2022)
The article reveals the features of forming the image of the border city Kharkiv, which is in conditions of unprovoked aggression. It is shown how various creative ideas and artistic techniques are used to convey to the people of other cities and countrie